Analysis Of The Effect Of Primary Pully Inclination Angle On The Torque Of The 115 CC Mio Sporty Motorcycle Engine - Muhammad Lyan Syaputra (METALOGRAM, 2024)
This test was conducted to determine the comparison of torque on a 115 cc motorcycle, Standard with different pully degree variations, 14 °, 13.5 °, 13 °, 12 °. With the maximum speed in each different pully test, at the 14 ° degree pully the resulting torque is averaged 6.35 with Rpm 6,637 (The trotle opening is maximum), In the 2nd test using Pully 13.5 ° testing was carried out with Rpm at 5. 900 - 5,980 (Maximum trotle gas opening) produced a torque of 6.47 which is greater than the test using the previous 14 ° pully, but the maximum Rpm produced by the pully with a degree of 13.5 ° mala is slower than testing using a 14 ° pully. From this test, we can see the difference. That using Pully 13.5° the torque is greater but the engine rotation is slower. The 3rd test using a 13 ° pully with a maximum Rpm at 6,500 - 6,700 (maximum trotle opening) produces a torque of 6.29, from this test it can be seen the difference in torque and Rpm produced by a 13.5 ° degree pully with a 13 ° degree pully, where the Rpm is 720 Rpm faster with a difference in torque at a lower rate of 0.18 Nm isbanding diangaka difference with a 13.5 ° degree pully. The 4th test using a 12° pully with a maximum Rpm at 7,140 - 7,190 Rpm (Maximum Gas Trotle Opening) produced a torque of 6.02. From this test, it can be seen the difference with the test using a 13° pully, where the Rpm produced is higher but the torque is smaller, the torque difference is 0.27.